A postmodern Christology with Christ but without the Son of God? - P, D. (Hervormde teologiese studies, 1993)
In this review article, the revisioned christology developed by the American theologian Mark Kline Taylor in the chapter ‘Christ as rough Beast’ in his book ‘Remembering Esperanza’ (1990) is discussed critically. The cultural- political theology developed by Taylor, in which he ‘moves’ from autobiographical elements to theological reflection in addressing the postmodern trilemma in North America, is explained. It is shown how Taylor, through his cultural-political hermeneutics of tradition, unfolds his christology as a fourfold christology in which Christ designates an intersubjective, socio-historical force for reconciliatory emancipation. Finally, his christological interpretation is critically compared by means of formal similarities with that of the German New Testament scholar Rudolf Bultmann (1884-1976).